Reflective practice in practice - Magnaye, Alejandro D.; Isidro, Rowena Vargas (Imus, Cavite Philippines : Eduheart Book Publishing, 2022)
This book was written by various authors in different disciplines to make us aware that reflection in our daily lives is significant to our personal and professional growth and development.
Title Page -- Copyright Page -- Acknowledgements -- Foreword -- Preface -- Table of contents -- 1. Alejandro D. Magnaye -- 2. John Paul J. Petrola -- 3. Gabriel S. Cabardo -- 4. Virginia Dulay-Akiate -- 5. Michael John Irog -- 6. Ivy D. Villanueva -- 7. John Paul T. Solon -- 8. Juri Fiel Kane P. Catungal -- 9. Gilmore Macarandang Rioveros -- 10. Francis O. Pantino -- 11. Jay A. Sario -- 12. Alfe M. Solina -- 13. Prof. Analuz A. Fuentebella -- 14. Dr. Ericson Matias -- 15. Dr. Aiza Violet B. Alfaro -- 16. Marlene P. Viernes -- 17. Nelarose Flores Steel -- 18. Dr. Dexter A. Soguilon -- 19. Ethel Reyes-Chua -- 20. Omar B. Jordan.
Includes bibliographical references.
Keywords: REFLECTIVE TEACHING